Legal Protection for Minors who are Victims of Criminal Sexual Abuse Committed by Their Own Biological Father (Case Study in Kedadi Village, Lebaksiu Subdistrict, Tegal Regency) - Siti Duwi Lestari (Proceedings Series on Social Sciences & Humanities, 2023)
Sexual abuse of minors is a serious and complex issue in today's society. This research aims to analyze the impact of sexual abuse on minors and explore effective countermeasures. This research uses a qualitative approach with a case study method to gain an in-depth understanding of the issue. The research involved participants of child victims of sexual abuse, their families, as well as professionals and parties involved in handling these cases, such as child protection agencies, police, and hospitals. Data were collected through in-depth interviews, observation, and analysis of relevant documents. The results of this study provide insights into the psychological, social and emotional impacts experienced by child victims of sexual abuse. These findings are integrated with the perspectives of families and professionals involved in handling these cases. In addition, this research also explores the coping strategies that have been put in place and the challenges faced in an effort to provide protection, recovery and justice for child victims. By understanding the impact experienced by victims of sexual abuse and looking at the challenges faced in handling these cases, this research provides valuable insights for professionals and practitioners involved in social work, child protection, psychology and law. It is hoped that the findings of this study can serve as a foundation for the development of more effective policies and intervention programs that can help prevent child sexual abuse and provide better protection for affected victims.